KONTRIBUSI USAHA TRANSPORTASI â€œOJEK PERAHUâ€ TERHADAP PENDAPATAN RUMAH TANGGA DI KELURAHAN SINDULANG KECAMATAN TUMINTING KOTA MANADO - Ruauw, Fernanda Grasela; Andaki, Jardie A.; Tambani, Grace O. (Universitas Sam Ratulangi, 2018)
AbstractBoats are the choice for transportation activities on the river. The condition of the Tondano River, specifically at the river mouth is suitable for boat crossings. The need to move from one side of the river to the other side of the river with various needs, raises remuneration for